2018
DOI: 10.1186/s12886-018-0970-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of color blindness among school children in three primary schools of Gish –Abay town district, Amhara regional state, north-west Ethiopia

Abstract: BackgroundAlthough there are limited studies, recent data are lacking to accurately determine the magnitude of color blindness in Ethiopia and there is no evidence of such a study in Gish Abay town district. The purpose of thie study was to assess the prevalence of color blindness among school children in Gish Abaya town district, Ethiopia.MethodsThe study used a community-based analytical cross-sectional study design with multistage cluster random sampling technique from September to October 2016. Three prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…However our results were higher than a few studies like 2.9% in (Mahajan and Gogna, 1977) ,2.5% in (Gupta et al, 2017), 2.1% in (Agarwal and Bansod, 2014), 2.02% in (Chandak et al, 2017), 1.4% in (Basavaraj et al, 2019), and lower than the prevalence rate of Manipuri Muslims (Shah et al, 2013) which was 5.28%. On comparing our results with the studies done across the world, near similar results were found in studies like 4.1% in (Woldeamanuel and Geta, 2018), 4.24% in (Wale et al, 2018). Further, there are few studies with Low prevalence rate, like 3.8% in (Niroula and Saha, 2010), 2.1% in (Shrestha et al, 2010), 2.6% in (Tabansi et al, 2008), 2.5% in (Oduntan et al, 2019), 2.3% in (Ugalahi et al, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…However our results were higher than a few studies like 2.9% in (Mahajan and Gogna, 1977) ,2.5% in (Gupta et al, 2017), 2.1% in (Agarwal and Bansod, 2014), 2.02% in (Chandak et al, 2017), 1.4% in (Basavaraj et al, 2019), and lower than the prevalence rate of Manipuri Muslims (Shah et al, 2013) which was 5.28%. On comparing our results with the studies done across the world, near similar results were found in studies like 4.1% in (Woldeamanuel and Geta, 2018), 4.24% in (Wale et al, 2018). Further, there are few studies with Low prevalence rate, like 3.8% in (Niroula and Saha, 2010), 2.1% in (Shrestha et al, 2010), 2.6% in (Tabansi et al, 2008), 2.5% in (Oduntan et al, 2019), 2.3% in (Ugalahi et al, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…These frequencies are relatively low compared to recent study done by Mitiku et al [2] among university students at Hawassa, Ethiopia. A comparable frequency of deutan and protan are reported in done in Gish-Abay town by Wale et al [19]. The slight difference in the prevalence could be due to genetic, geographic, population movements and cultural/religious factors [2,12,18].…”
Section: Discussionsupporting
confidence: 60%
“…In addition, in some fields of studies such as electrical engineering, agriculture, laboratory, forensic sciences, chemical engineering, soil engineering and architectural engineering normal colour vision is important [2,13,22]. In Ethiopia, there are a limited number of studies done to assess the prevalence of congenital colour vision deficiency and its potential professional impacts [23][24][25][26][27][28]. The objective of the present study was to assess the prevalence and allele frequencies of red-green colour vision defects among students at Hawassa University, Ethiopia.…”
Section: Introductionmentioning
confidence: 99%